Dietary habits and cognitive performance in primary school students: a cross-sectional study in Khemisset region in Morocco - Elkhatir, Mohcin; Ghaffouli, Chaymae; Louasté, Bouchra; Loukili, Abdechahid; Aboussaleh, Youssef (Frontiers in Nutrition, 2025)
BackgroundIn children, cognitive performance is influenced by dietary habits, health status, and socioeconomic factors. Poor diets, especially high intakes of ultra-processed foods, together with psychological stress and learning difficulties, can impair attention and concentration in school-aged children. It is critical to comprehend these interactions. It supports improved long-term health and educational outcomes.MethodsA cross-sectional survey was conducted among primary school students in the region of Khemisset, Morocco. Socioeconomic parameters, dietary habits, health status, visual problems, psychological stress, and learning difficulties were assessed via questionnaires completed with parental consent. Cognitive performance was assessed via the d2R test, which measures processing speed, concentration, and accuracy.ResultsOf the 330 students (53.9% girls, 46.1% boys), the majority had a BMI of less than 18.5 (59.7%). Most reported no health problems (91.2%) or vision problems (89.4%), while 32.7% experienced psychological stress and 43% had learning difficulties. In terms of dietary habits, 66.9% of participants ate three or more meals per day, but 60% skipped breakfast. The d2R test results revealed that higher meal regularity and breakfast consumption were associated with better processing speed, concentration, and accuracy.ConclusionThis study highlights the significant influence of dietary habits and lifestyle factors on cognitive performance among primary school students. Regular meal consumption, particularly breakfast, was positively associated with increased attention, concentration, and processing accuracy. In contrast, high intake of ultra-processed foods and the presence of psychological stress and learning difficulties were linked to poorer cognitive outcomes.